Extraction, physicochemical properties, and antioxidant activity of natural melanin from Auricularia heimuer fermentation - Ma, Yinpeng; Zhang, Piqi; Dai, Xiaodong; Yao, Xiuge; Zhou, Shuyang; Ma, Qingfang; Liu, Jianing; Tian, Shuang; Zhu, Jianan; Zhang, Jiechi; Kong, Xianghui; Bao, Yihong (Frontiers in Nutrition, 2023)
In this study, single-factor experiments, Box-Behnken design (BBD), and response surface methodology (RSM) were employed to investigate the effects of alkali-soluble pH, acid precipitation pH, and microwave time on the extraction yield of Auricularia heimuer melanin (AHM) from fermentation. Ultraviolet-visible spectrum (UV-Vis), Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscope (SEM), and high-performance liquid chromatography (HPLC) were used to analyze the extracted AHM. The solubility, stability, and antioxidant activities of AHM were also measured. The results showed that alkali-soluble pH, acid precipitation pH, and microwave time significantly affected the AHM yield, with the following optimized microwave-assisted extraction conditions: alkali-soluble pH of 12.3, acid precipitation pH of 3.1, and microwave time of 53 min, resulting in an AHM extraction yield of 0.4042%. AHM exhibited a strong absorption at 210 nm, similar to melanin from other sources. FT-IR spectroscopy also revealed that AHM exhibited the three characteristic absorption peaks of natural melanin. The HPLC chromatogram profile of AHM showed a single symmetrical elution peak with a 2.435 min retention time. AHM was highly soluble in alkali solution, insoluble in distilled water and organic solvents, and demonstrated strong DPPH, ·OH, and ABTS free radical scavenging activities. This study provides technical support to optimize AHM extraction for use in the medical and food industries.